2023
DOI: 10.3390/pathogens12070894
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Merkel Cell Polyomavirus (MCPyV) DNA and Transcripts in Merkel Cell Carcinoma (MCC)

Abstract: Merkel cell polyomavirus (MCPyV) is the etiological agent of the majority of Merkel cell carcinoma (MCC): a rare skin tumor. To improve our understanding of the role of MCPyV in MCCs, the detection and analysis of MCPyV DNA and transcripts were performed on primary tumors and regional lymph nodes from two MCC patients: one metastatic and one non-metastatic. MCPyV-DNA was searched by a quantitative polymerase chain reaction (qPCR), followed by the amplification of a Large T Antigen (LTAg), Viral Protein 1 (VP1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…However, since the detection and quantitation of viral DNA as well as the characterization of NCCR and VP1 regions are not sufficient to define the MCPyV role in oral malignancies, further analyses have been performed. In spite of what has been reported for virus-positive MCCs, where viral replication is hampered, late genes are not expressed [39,48], and transcript analysis revealed both LT and VP1 gene expression in all virus-positive samples, supporting viral replication activity in our samples.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, since the detection and quantitation of viral DNA as well as the characterization of NCCR and VP1 regions are not sufficient to define the MCPyV role in oral malignancies, further analyses have been performed. In spite of what has been reported for virus-positive MCCs, where viral replication is hampered, late genes are not expressed [39,48], and transcript analysis revealed both LT and VP1 gene expression in all virus-positive samples, supporting viral replication activity in our samples.…”
Section: Discussioncontrasting
confidence: 50%
“…To date, several studies reported viral integration in the host genome and the expression of a truncated LT gene with a preserved LXCXE motif, able to bind and sequestrate pRb as key players in MCPyV-mediated oncogenesis [24,39,48]. In our MCPyV-positive samples, viral integration was not reported and a full-length LT, retaining both pRb and p53 binding domains, was observed.…”
Section: Discussionmentioning
confidence: 60%